Effect of fly ash on microstructural and resistance characteristics of dredged sediment stabilized with lime and cement. (22nd February 2021) - Furlan, Ana Paula; Razakamanantsoa, Andry; Ranaivomanana, Harifidy; Amiri, Ouali; Levacher, Daniel; Deneele, Dimitri
Graphical abstract: Highlights: FA acts as filler when incorporated with sediment at early age. FA promotes nucleation, cementitious compound growth resulting in porosity refinement. FA reduces shrinkage and increases strength gain of mixtures, regardless curing time. The effectiveness of FA addition is confirmed when used with sediment-lime and sediment-cement. Abstract: This study deals with the definition of an efficient combination of fly ash (FA) with lime or cement and with both, to improve the dredged sediment (DS) properties. At early age, filler and nucleation effects of FA lead to a refinement of the microstructure in addition to the macro porosity reduction induced by lime and cement. At long term, the microstructure becomes denser due to the pozzolanic property of FA. At macroscale, DS stabilized using FA show lower shrinkage and higher mechanical resistance than that stabilized without FA, with more pronounced effects when FA is mixed with cement.